Role of Nanotechnology in Alcohol Detection - Sweta Verma (International Journal of Medical Toxicology and Legal Medicine, 2024)
In the field of forensic science, the precise and timely identification of alcohol plays a pivotal role in investigating incidents like accidents, crimes, and fatalities. This review study introduces an innovative approach to alcohol detection within forensic settings by incorporating nanomaterials as sensing agents. Nanomaterials, distinguished by their exceptional surface properties and heightened reactivity, present an advanced foundation for the swift and sensitive detection of alcohol. The proposed technique not only surpasses traditional forensic methods but also opens avenues for on-site, real-time analysis. This investigation represents a transformative shift in forensic alcohol detection, offering more effective, precise, and adaptable tools for criminal inquiries and legal proceedings.